Rethinking Teacher Education for the 21st Century Trends, Challenges and New Directions - Danilewicz, Wioleta; Korzeniecka-Bondar, Alicja; Kowalczuk-Walędziak, Marta; Lauwers, Gracienne Maria Louisa Veronica (Verlag Barbara Budrich, 2019)
This book focuses on current trends, potential challenges and further developments of teacher education and professional development from a theoretical, empirical and practical point of view. It intends to provide valuable and fresh insights from research studies and examples of best practices from Europe and all over the world. The authors deal with the strengths and limitations of different models, strategies, approaches and policies related to teacher education and professional development in and for changing times (digitization, multiculturalism, pressure to perform).